Fenretinide differentially modulates the levels of long- and very long-chain ceramides by downregulating Cers5 enzyme: evidence from bench to bedside - Garić, Dušan; De Sanctis, Juan B; Wojewodka, Gabriella; Houle, Daniel; Cupri, Shanon; Abu-Arish, Asmahan; Hanrahan, John W; Hajduch, Marian; Matouk, Elias; Radzioch, Danuta (Journal of molecular medicine (Berlin, Germany), 2017)
UNLABELLED: Cystic fibrosis is the most common genetic disease, in which symptoms may be alleviated but not fully eliminated. Ceramides have long been implicated in the inflammatory etiology of cystic fibrosis, with contradicting reports with regards to their role. Recently, significant biological and biophysical differences have been observed between long- and very long-chain ceramides. This work reveals that long-chain ceramides are upregulated whereas very long-chain ceramides are downregulated in cell lines, mouse animal model, and patients with cystic fibrosis, compared with their controls. Treatment with fenretinide decreases the levels of long-chain ceramides and increases the levels of very long-chain ceramides. Our results show that restoration of cystic fibrosis conductance regulator (CFTR) expression is associated with normalization of aberrant levels of specific ceramides. This demonstrates for the first time a correlation between CFTR protein expression and regulation of specific ceramide levels. Furthermore, using cystic fibrosis lung epithelial cell lines, we demonstrate that this effect can be attributed to the transcriptional downregulation of ceramide synthase 5 (Cers5) enzyme. We also discovered a partial synergism between fenretinide and zinc (Zn2+), which deficiency has been reported in patients with cystic fibrosis. Overall, in addition to having direct translational application, we believe that our findings contribute to the understanding of ceramide metabolism in cystic fibrosis, as well as other inflammatory diseases where imbalances of ceramides have also been observed. KEY MESSAGES: Long- and very long-chain ceramides (LCCs and VLCCs) are biochemically distinct. LCCs are upregulated whereas VLCCs are downregulated in cystic fibrosis. Fenretinide downregulates the levels of LCCs and upregulates the levels of VLCCs. Fenretinide changes the balance of LCCs and VLCCs by downregulating Cers5 enzyme. Fenretinide and zinc ions cooperate in the modulation of ceramide levels.
Keywords: Humans; lidé středního věku; Down-Regulation; Female; mladý dospělý; dospělí; Fenretinide; Ceramides; lidé; zvířata; down regulace; myši inbrední C57BL; buněčné linie; myši knockoutované; Adult; Transcriptional Activation; aktivace transkripce; Cystic Fibrosis; ženské pohlaví; Cell Line; fenretinid; Male; Mice, Knockout; Middle Aged; ceramidy; Adolescent; Mice, Inbred C57BL; Sphingosine N-Acyltransferase; cystická fibróza; Young Adult; PPAR gama; sfingosin-N-acyltransferasa; Animals; mužské pohlaví; Cystic fibrosis; Disease Models, Animal; PPAR gamma; mladiství; modely nemocí na zvířatech